Pilot Experience with ABO-Incompatible Kidney Transplantation as a Second Transplant - Uchida, Junji (Urol Int, 2019)
BACKGROUND: Despite advances in immunosuppressant medications, improvement in long-term survival for kidney transplant recipients has been more difficult to achieve. In fact, the number of patients with failing grafts who must either return to dialysis or undergo a second transplant is increasing. Second transplantation is associated with reduced mortality rates compared to remaining on dialysis after an initial graft loss. Nowadays, excellent ABO-incompatible kidney transplant outcomes have been achieved. However, there have been no reports on ABO-incompatible kidney transplantation as a second transplant. PATIENTS AND METHODS: Three patients who received their graft from an ABO-incompatible living donor at our institution as a second transplant were enrolled in this study. We focused on immunosuppressive therapy for second ABO-incompatible kidney transplantation, donor-specific antibody status before the second transplant, patient and graft survivals, and complications. RESULTS: All 3 patients successfully underwent ABO-incompatible kidney transplantation as a second transplant with a follow-up period of 141, 39, and 24 months. Patient and graft survival rates were 100%. CONCLUSIONS: ABO-incompatible kidney transplantation may be an acceptable treatment for patients who need a second renal replacement therapy after their initial graft failure.